2008
DOI: 10.1038/sj.bjc.6604781
|View full text |Cite
|
Sign up to set email alerts
|

Combined assessment of EGFR pathway-related molecular markers and prognosis of NSCLC patients

Abstract: The purpose of this study is to evaluate the prognostic value of the combined assessment of multiple molecular markers related to the epidermal growth factor receptor (EGFR) pathway in resected non-small cell lung cancer (NSCLC) patients. Tumour specimens of 178 NSCLC patients were collected and analysed for EGFR and KRAS mutation status by DNA sequencing, and for EGFR copy number by fluorescent in situ hybridisation. Tissue microarrays were generated and used to determine the expression of multiple EGFR pathw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
22
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 45 publications
1
22
1
Order By: Relevance
“…Previous studies have shown that the above markers could not only predict the efficacy of TKI treatment but the prognosis of NSCLC [16][17][18][19]. However, little is known about correlations between the status of these kinases involved in the EGFR pathway and the effectiveness of adjuvant chemotherapy in postoperative NSCLC.…”
mentioning
confidence: 95%
“…Previous studies have shown that the above markers could not only predict the efficacy of TKI treatment but the prognosis of NSCLC [16][17][18][19]. However, little is known about correlations between the status of these kinases involved in the EGFR pathway and the effectiveness of adjuvant chemotherapy in postoperative NSCLC.…”
mentioning
confidence: 95%
“…EGFR protein expression intensity was determined using IHC and scored visually, that is, semiquantitatively, as described previously (19).…”
Section: Immunohistochemistrymentioning
confidence: 99%
“…Alteration of the major regulatory pathways either by gene overexpression or mutation is a frequent event in lung cancer. It is widely accepted that epidermal growth factor receptor (EGFR), K-Ras, and mitogen-activated protein kinase function sequentially in the EGFR signaling pathway and this pathway plays a fundamental role in NSCLC (3,4). K-ras oncogene is frequently mutated in human tumors and activating mutations in K-ras occur in 30% of NSCLC.…”
Section: Introductionmentioning
confidence: 99%